1990
DOI: 10.1203/00006450-199012000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Brain Superoxide Anion Generation during Asphyxia and Reventilation in Newborn Pigs

Abstract: Perinatal asphyxia can occur in babies and may result in death, or damage to brain and other organs. Sequelae of brain damage are cerebral palsy, mental retardation, and epilepsy. The exact mechanisms that lead to brain damage are not known with certainty, but activated oxygen species, if produced, could be involved. Oxygen free radicals can damage or kill cells via several pathways, which include lipid peroxidation of membranes and inactivation of enzymes and transport proteins and DNA and RNA alterations (1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1993
1993
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…In addition, the 1-to 6-d age precedes the period of peak myelination in pig brain (29), thereby approximating a human newborn. In prior studies of asphyxia in immature piglets, the length of asphyxia often was determined as the time required to achieve a predetermined reduction in heart rate or blood pressure, which generally varied from 2 to 7 min (25)(26)(27)(28). In preliminary studies in our laboratory, we found that heart rate and mean arterial blood pressure responses to brief asphyxia in immature piglets were too variable to achieve a consistent degree of asphyxia.…”
Section: P1 Asphyxiamentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, the 1-to 6-d age precedes the period of peak myelination in pig brain (29), thereby approximating a human newborn. In prior studies of asphyxia in immature piglets, the length of asphyxia often was determined as the time required to achieve a predetermined reduction in heart rate or blood pressure, which generally varied from 2 to 7 min (25)(26)(27)(28). In preliminary studies in our laboratory, we found that heart rate and mean arterial blood pressure responses to brief asphyxia in immature piglets were too variable to achieve a consistent degree of asphyxia.…”
Section: P1 Asphyxiamentioning
confidence: 96%
“…The immature piglet was felt to be an appropriate model for this study because of previous use in studies involving pediatric cardiopulmonary resuscitation (19,23,24) and in studies examining cerebral blood flow, cerebral lipid peroxidation, and Na+,K+-ATPase loss after asphyxia (25)(26)(27)(28). In addition, the 1-to 6-d age precedes the period of peak myelination in pig brain (29), thereby approximating a human newborn.…”
Section: P1 Asphyxiamentioning
confidence: 99%
“…In normoxia, COX-derived metabolites play an important role in the control of VSM in many cerebrovascular regulatory pathways (3). In contrast, uncontrolled COX-activity under hypoxic/ischemic stress may be an ample source of superoxide anions and proinflammatory prostanoids involved in cellular injury and cell death (4,5). In fact, COX-inhibitors have pronounced neuroprotective effects in many neonatal and adult experimental models of hypoxia and stroke.…”
mentioning
confidence: 99%
“…SOD has also been shown to prevent ischemia/reperfusion injury and neurologic damage in animal models of IVH, suggesting that oxygen radical injury is important in the pathogenesis of neurologic injury in premature infants. 7,15,16 Preliminary reports from a recently completed multicenter, placebo-controlled trial of multiple doses of rhSOD in 301 very low birth weight infants indicate that rhSOD treatment is associated with approximately a 60% decrease in the incidence of severe (grades III and IV) IVH and periventricular leukomalacia, which is known to affect long-term neurodevelopmental outcome. 3,11,12,17 Further demonstrable evidence of the role of rhSOD in preventing severe neonatal pulmonary and neurologic injury will need to await both the short-term and long-term results of multicenter controlled trials with larger number of enrolled infants.…”
Section: Discussionmentioning
confidence: 99%